2016
DOI: 10.1039/c6nj02193j
|View full text |Cite
|
Sign up to set email alerts
|

Cu(ii) complex of a new isoindole derivative: structure, catecholase like activity, antimicrobial properties and bio-molecular interactions

Abstract: An isoindole based trigonal bipyramidal Cu(ii) complex shows catecholase and antimicrobial activities. It interacts with bio-relevant antipyrine derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…8 In another article, the same group reported the catalysis and antimicrobial activities of the copper complex. 12 Kumar et al reported dual catalysis and dual sensing behavior of a copper-based metal–organic framework. 13 Following such previous instances, herein, we have investigated the bifunctional activities of complex 1 .…”
Section: Introductionmentioning
confidence: 99%
“…8 In another article, the same group reported the catalysis and antimicrobial activities of the copper complex. 12 Kumar et al reported dual catalysis and dual sensing behavior of a copper-based metal–organic framework. 13 Following such previous instances, herein, we have investigated the bifunctional activities of complex 1 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Among the plethora of Cu (II) compounds that have been tested as anticancer agents, complexes with Schiff base ligands have emerged as promising candidates. [9][10][11][12][13] Since the pioneering work of Reedijk et al 14,15 on Schiff base derivatives of pyrimol with copper and other metals, several groups have assessed the DNA cleavage, cytotoxicity and apoptosis induction activities of related families of copper complexes. [16][17][18] Additionally, there is a current interest in the development of paramagnetic complexes to be used as relaxation agents for contrast in magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%